Relationship Between Emotional Intelligence and Foreign Language Learning - Tekin, Abdulkadir; Yıldırım, Halil; Yıldırım, Osman (Int Scientific Conference SGEM, 14, Kilment Ohridsky BLVD, Sofia, 1797, Bulgaria, 2008)
The increasing number of recent researches indicates that emotional intelligence is more important than IQ in many fields. In literature, many quantitative findings indicate that there is a significant relationship between academic achievement and emotional intelligence skills. In other words, analysis indicates that emotional intelligence skills can serve as a indicator of academic achievement and effective learning. The main focus of this research is to discuss the relationship between emotional intelligence skills and academic achievement in foreign language and explore how their relationship may influence language learning. The sample data for this research is 372 School of Vocational Studies students in Istanbul. Thus, this research aimed at exploring the relationship between academic achievement (effective learning) and emotional intelligence skills. In the research, participants emotional intelligence was assessed by the Emotional Competence Inventory (ECI, 2nd Version) developed by Boyatzis and Goleman. According to the results, a strong relationship (r>0,40) was found between academic achievement and emotional intelligence skills.
Keywords: emotional intelligence; academic achievement; language learning